Efektivitas Terapi Kognitif Perilaku dalam Menurunkan Risiko Relapse Pecandu Narkoba yang Menjalani Rehabilitasi di Sumatera Utara: Penelitian - Endah Carina Br Saragih; Hasnida; Rahma Fauzia (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Drug abuse is a multidimensional problem that remains a serious issue in Indonesia, as indicated by the increasing prevalence of narcotics users and the high rate of relapse among former addicts after rehabilitation. One of the psychosocial interventions implemented by the National Narcotics Board (BNN) in addressing drug addiction is Cognitive Behavior Therapy (CBT), which focuses on cognitive restructuring and the modification of maladaptive behaviors. This study aims to examine the effectiveness of CBT in reducing relapse risk among drug addicts undergoing rehabilitation in North Sumatra. The study employed a quantitative approach using a true experimental design, specifically a pretest–posttest control group design. The participants consisted of seven residents with drug addiction at the Titian Harapan Indonesia Foundation, Deli Serdang Regency, who were selected using a simple random sampling technique. Relapse risk was measured using the AWARE (Advance Warning of Relapse) scale before and after the CBT intervention, which was administered over five sessions. Data analysis was conducted using N-Gain score calculations. The results indicated a significant reduction in relapse risk scores among all participants, with an N-Gain value of -0.6583, which falls within the moderate category. These findings suggest that CBT is effective in reducing relapse risk by enhancing cognitive awareness of triggers, automatic thoughts, and emotional responses associated with addictive behavior. However, the moderate level of effectiveness indicates that CBT requires additional reinforcement, particularly in the form of practical and applicable coping skills, to enable participants to manage stress and high-risk situations independently in their daily lives.